2020
DOI: 10.3892/ol.2020.11957
|View full text |Cite
|
Sign up to set email alerts
|

Effects of miR‑218‑1‑3p and miR‑149 on proliferation and apoptosis of non‑small cell lung cancer cells

Abstract: The aim of the present study was to explore the effects of miR-218-1-3p and miR-149 on the biological function of non-small cell lung cancer (NSCLC) cells A549. Paired NSCLC and adjacent tissues were obtained from 50 NSCLC patients admitted to Shandong Provincial Chest Hospital Affiliated to Shandong University (Jinan, China) from April 2015 to May 2018. The expression levels of miR-218-1-3p and miR-149 were detected by reverse transcription-quantitative PCR (RT-qPCR). The lung adenocarcinoma A549 cells were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Importantly, our data illustrate that overexpression of miR-218-1-3p inhibits CTSB secretion in BMI1 expressing cells, while its expression also affects their invasion and trans-intrahepatic biliary epithelial migration ability. In support of this finding, Guo et al shows that miR-218-1-3p regulates lung cancer cell invasiveness 41 , while its expression has been linked with epithelial mesenchymal transition and angiogenesis in colorectal cancer 42 . We also discover that miR-218-1-3p overexpression reduces jaundice, gall bladder and bile duct enlargement and BDTT in WB BMI1 implanted mice, independent of primary orthotopic liver tumor growth.…”
Section: Discussionmentioning
confidence: 84%
“…Importantly, our data illustrate that overexpression of miR-218-1-3p inhibits CTSB secretion in BMI1 expressing cells, while its expression also affects their invasion and trans-intrahepatic biliary epithelial migration ability. In support of this finding, Guo et al shows that miR-218-1-3p regulates lung cancer cell invasiveness 41 , while its expression has been linked with epithelial mesenchymal transition and angiogenesis in colorectal cancer 42 . We also discover that miR-218-1-3p overexpression reduces jaundice, gall bladder and bile duct enlargement and BDTT in WB BMI1 implanted mice, independent of primary orthotopic liver tumor growth.…”
Section: Discussionmentioning
confidence: 84%
“…miR-149 is a well-known tumor regulator that is dysregulated in various cancers, including oral squamous cell carcinoma, digestive system cancers, and lung cancer. [20][21][22] Several target genes of miR-149 have been identified, including FASLG, caspase-2, AKT1, PARP-2, and FOXM1. 23 In previous research, miRNA-149 was found to be an oncogenic regulator in ALL.…”
Section: Discussionmentioning
confidence: 99%
“…93 Guo et al found that miR-149 strongly inhibited the growth of nonsmall cell lung cancer (NSCLC) and promoted its apoptosis. 94 However, Xiao et al gave a different evidence that exosomal miR-92a-1-5p was down-regulated while exosomal miR-424-3p and miR-149-3p were significantly up-regulated in RCC. 87 MiRNAs could play an opposite role in different cancers, but it is thought-provoking that there are differences in expression patterns between exosomes and cell lines of the same cancer.…”
Section: Dovepressmentioning
confidence: 99%